Binaural Interaction in Human Auditory Steady State Response - Aoki, Kimie; Suzuki, Tokuro; Kobayashi, Kiyoko (AUDIOLOGY JAPAN, 1989)
Binaural interaction (BI) in auditory 49-Hz steady state responses (SSR) was investigated in 13 adult subjects with normal hearing. Two kinds of SSR were recorded mostly during sleep. They were elicited with sinusoidally amplitude-modulated tones at 500Hz or with tone-pips of 2-1-2 cycles at the same frequency. Auditory brainstem response (ABR) and middle latency response (MLR) to the same tone-pips were also recorded at a stimulus interval of 115ms. BI was represented numerically in the ratio in amplitudes of binaurally evoked responses to summed monaural responses for the two ears. The mean values of BI measured from ABR, MLR (Pa component), SSR elicited with amplitude-modulated tones and with tone-pips were 0.945, 0.773, 0.898 and 0.871, respectively. Significant difference was found between the BI-values in MLR (Pa) and each of other 3 responses. Lack of significant difference in the BI-values between SSRs and ABR strongly suggested that ABR was the most important component in SSR during sleep.